Los conceptos estructurales en el aprendizaje por investigación - Gagliardi, Raúl (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
As a contribution to the making of a new didactical model, this paper faces the following questions: — Which are the mechanisms to understand the learning process? — Which are the pedagogical issues and strategies that may facilitate learning? Specific instances from the teaching of Biology are used.